Psychosocial Resources (Social Support and School) and Physical Activity During Free Time Among High-School Students - Ilona Karácsony; Gabriella Hideg-Fehér (Social Sciences)
Background: During childhood and adolescence, personality development is continuous. Younger people—defined in this study as high-school students aged 14 to 18—are particularly receptive to change. The health behaviors formed during this period can significantly influence health in later life. Therefore, families and schools play a crucial role in promoting a healthy lifestyle. In our research, we examined the relationship between psychosocial resources (social support and school resources) and the regularity and intensity of physical activity. Methods: In this study, “appropriate physical activity” refers to the level and intensity of activity recommended by the World Health Organization—namely, at least 60 min per day of moderate- to vigorous-intensity aerobic activity for adolescents. We conducted our cross-sectional research in Hungary, Western Transdanubia, using convenience sampling among high-school students (n = 331). Data collected with a self-edited and standardized questionnaire (MSPSS, HBSC school resources and school social support) were analyzed using the SPSS Statistics 22 program with a t-test, ANOVA and χ2 test (p < 0.05). Results: In the case of the time spent on physical activities per week, boys (p < 0.05) and younger people (p < 0.05) showed a much more favorable picture. Examining the intensity of regular physical activity among students who belonged to the appropriate range, the average values of family social support were significantly higher (p < 0.05), but this association was not observed for social support from friends or significant others (p > 0.05). The amount of movement was not differentiated by support from others (p > 0.05). The level of attitude towards their school was higher among students who performed physical activity of the appropriate quality and quantity (p < 0.05). Teachers’ assessment of school performance and the quality of the relationship with teachers showed a correlation with physical activity performed at the appropriate intensity (p < 0.05). Conclusions: We found a positive effect of family and school resources on the regularity and intensity of physical activity, which draws attention to strengthening the partnership between family and school, improving the school atmosphere and social support within the school, increasing students’ attachment to their institution. The combination of these resources can help children lead a more active and healthier life, which has a beneficial long-term impact on their physical and mental well-being. The cooperation between parents and schools is crucial in supporting young people in adopting a healthy lifestyle.